Metal bioaccumulation and metallothionein concentrations in larvae of Crassostrea gigas - Damiens, Gautier; Mouneyrac, Catherine; Quiniou, Francoise; His, Edouard; Gnassia Barelli, Mauricette; Romeo, Michèle (Environmental Pollution, 2006)
Larval stages of bivalve molluscs are highly sensitive to pollutants. Oysters from a hatchery from Normandy (English Channel) were induced to spawn, and fertilized eggs were exposed to copper or cadmium for 24 h. Metal accumulation (from 0.125 to 5 mu g Cu L-1 and from 25 to 200 mu g Cd L-1) and MT concentrations were measured in larvae. Compared to controls, larvae accumulated copper and cadmium with an increase in MT concentrations particularly with cadmium (i.e. 130.96 ng Cu (mg protein)(-1) and 12.69 mu g MT (mg protein)(-1) at 1 mu g Cu L-1 versus 23.19 ng Cu (mg protein)(-1) and 8.92 mu g MT (mg protein)(-1) in control larvae; 334.3 ng Cd (mg protein)(-1) and 11.70 mu g MT (mg protein)(-1) at 200 mu g Cd L-1 versus 0.87 ng Cd (mg protein)(-1) and 4.60 mu g MT (mg protein)(-1) in control larvae). Larvae were also obtained from oysters of a clean area (Arcachon Bay) and a polluted zone (Bidassoa estuary) and exposed to copper in the laboratory, their MT concentration was measured as well as biomarkers of oxidative stress. Biomarker responses and sensitivity to copper for the larvae from Arcachon oysters were higher than for those from Bidassoa.